Pengaruh Literasi Keuangan, Pelatihan Pasar Modal Terhadap Keputusan Investasi Di Pasar Modal Dengan Technology Informasi Sebagai Pemoderasi Di Galeri Investasi BEI UNHI - Ni Putu Dessy Wiadnyani; Ni Wayan Yuniasih; I Putu Deddy Samtika Putra (UNHI Press, 2025)
The capital market provides a platform for companies to raise funds from investors through financial instruments such as shares and bonds. This research examines the influence of financial literacy and capital market training on investment decisions, with information technology as a moderating variable. Financial literacy is crucial for understanding investment risks and opportunities, while capital market training enhances knowledge and skills. Information technology facilitates access to information but can also present challenges in decision-making. The study was conducted at the IDX Investment Gallery of UNHI, focusing on how technology moderates the relationship between financial literacy and capital market training on investment decisions. The data was collected through questionnaires from 90 active members of KSPM UNHI, using the PLS test for analysis. Results show that financial literacy has a significant positive effect on investment decisions, while capital market knowledge has a positive but insignificant impact. Information technology does not significantly moderate the relationship between financial literacy and investment decisions but negatively affects the impact of capital market knowledge. These findings highlight the importance of effective interaction between financial literacy, capital market knowledge, and information technology in making informed investment decisions.